Effect of changing female stimulus on intensive semen collection in young Murciano-granadina male goats - Silvestre, Miguel A.; Salvador, I.; Sanchez, J. P.; Gómez, Ernesto A. (2017)
The aim of this research was to study the effect of changing female stimulus on libido and semen characteristics from young Murciano-granadina male goats submitted to intensive semen collection using females not in estrus as teasers. Males were submitted to two different sexual stimulation procedures. In the first procedure, the same doe was used as the female stimulus for three consecutive presentations. In the second, the doe was replaced after the second presentation by a new female. Semen volume, concentration, forward progressive motility, and live spermatozoa were scored. To analyze reaction time (RT), three types of analysis were performed. In the first one, RT was analyzed by multifactor ANOVA, taking as a missing value 300 s when a buck did not ejaculate. In the second, RT also was analyzed by multifactor ANOVA, but data from males that did not ejaculate were removed. In the third, a Cox Survival analysis was carried out by censoring data when a buck did not ejaculate within 5 min of entering the test arena. A decrease in semen volume and sperm concentration in the successive ejaculations was observed, being highly marked in the third ejaculation independent of the stimulation procedure (0.62 vs. 0.38 and 0.43 mL, and 2,828 vs. 2,183 and 2,223 million spermatozoa/mL to the first and third ejaculation respectively; P < 0.05). No significant differences were observed either in forward progressive motility or live sperm rate. Changing the female stimulus in the third presentation had no significant effect on any seminal characteristic. Regarding libido and mounting behavior variables, there was a substantial decrease in RT in the third service when the female was changed (with both types of ANOVA). When censored data were taken into account, the relative risk showed that the probability of a male ejaculating in the third presentation increased almost fourfold when the female was replaced than when the female was the same in all services (P < 0.05). In conclusion, young Murciano-granadina bucks can be used as semen donors because none of the most important semen variables used to reject or accept an ejaculate before freezing process decreased after intensive semen collection. We also recommend changing the female stimulus to make the semen collection procedure more efficient and using survival analysis methodology to analyze time data, mainly when a high rate of censored data are scored.